Myanmar : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2013)
Myanmar is a low-income country, and with the right reforms, it can realize its rich economic potential. The government has embarked on a bold and historic set of reforms, which are already bearing fruit. Executive Directors support the steps for ensuring macroeconomic stability. Exchange rate unification will be an important foundational step for securing macroeconomic stability, which will help boost competitiveness and trade. A consistent monetary policy framework and containing fiscal deficits will give higher and stable revenues to fund development needs.